Evaluation of a 7‐Methoxycoumarin‐3‐carboxylic Acid Ester Derivative as a Fluorescent, Cell‐Cleavable, Phosphonate Protecting Group. Issue 1 (19th November 2015) - Wiemer, Andrew J.; Shippy, Rebekah R.; Kilcollins, Ashley M.; Li, Jin; Hsiao, Chia‐Hung Christine; Barney, Rocky J.; Geng, M. Lei; Wiemer, David F.
Abstract: Cell‐cleavable protecting groups often enhance cellular delivery of species that are charged at physiological pH. Although several phosphonate protecting groups have achieved clinical success, it remains difficult to use these prodrugs in live cells to clarify biological mechanisms. Here, we present a strategy that uses a 7‐methoxycoumarin‐3‐carboxylic acid ester as a fluorescent protecting group. This strategy was applied to synthesis of an ( E )‐4‐hydroxy‐3‐methyl‐but‐2‐enyl diphosphate (HMBPP) analogue to assess cellular uptake and human Vγ9Vδ2 T cell activation. The fluorescent ester displayed low cellular toxicity (IC50 >100 μm ) and strong T cell activation (EC50 =0.018 μm ) relative to the unprotected anion (EC50 =23 μm ). The coumarin‐derived analogue allowed no‐wash analysis of biological deprotection, which revealed rapid internalization of the prodrug. These results demonstrate that fluorescent groups can be applied both as functional drug delivery tools and useful biological probes of drug uptake. Abstract : Fluorescent protection : Small phosphonates face large barriers to cell entry. We therefore developed a biolabile fluorescent protecting strategy that allows for efficient payload delivery and simultaneous monitoring. These results show that bulky fluorescent systems can be tolerated by cellular esterases without loss of activity or generation of toxicity.